Pendidikan Kader Ulama (PKU) di IAIN Palangka Raya: Menyongsong Generasi Ulama Indonesia - Roziqin, Muhamad Arif; Prasongko, Wahyu Agung; Aisyah, Siti (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
Indonesia can be said to have now experienced a crisis of scholars in the current era. Therefore, there is a need for self-awareness as Muslims to educate and improve the situation. One of them is by preparing for the birth of the next generation of scholars such as holding a Cadre Ulama Education (PKU) regeneration program among students of the State Islamic Institute (IAIN) of Palangka Raya. The purpose of this study was to find out how the implementation of Ulama Cadre Education (PKU) at IAIN Palangka Raya in building a generation of prospective young scholars. The type in this research is using the type of field research orfield research. Then, the method used is a qualitative method. Qualitative methods are used to obtain and find detailed information about problems or phenomena that occur. The findings obtained in this study were PKU IAIN Palangka Raya students in building a generation of prospective young scholars, namely. First, by instilling an Islamic character in the younger generation. Second, instill an Islamic soul guided by the Al-Quran and hadith in behavior. Third, instill the soul of a generation of scholars who are ready to appear in the future.